Alterations of Vaginal Microbiota in Women With Infertility and Chlamydia trachomatis Infection - Chen, Hongliang; Wang, Li; Zhao, Lanhua; Luo, Lipei; Min, Shuling; Wen, Yating; Lei, Wenbo; Shu, Mingyi; Li, Zhongyu (Frontiers in Cellular and Infection Microbiology, 2021)
Chlamydia trachomatis (C. trachomatis) is the most common bacterial sexually transmitted infections (STIs) globally, causing serious sequelae such as pelvic inflammatory disease and infertility if ascending to the female upper genital tract. Previous studies have revealed the pivotal role of vaginal microbiota in susceptibility to STIs. Whereas the alterations in the vaginal microbiota in infertile women with C. trachomatis infection remains unknown. Here we examined the vaginal microbial profiles towards infertile women with C. trachomatis-negative, infertile women with C. trachomatis-positive, pre- and post-antibiotic treatment, recruiting healthy women with C. trachomatis-negative as references of eubiosis and dysbiosis, via metagenomic analysis of sequenced 16S rRNA gene amplicons. We found tubal infertile women with C. trachomatis infection had a peculiar vaginal microbiota dominated by L. iners than by L. crispatus, and experienced a decrease in Lactobacilli, Bifidobacterium, Enterobacter, Atopobium and Streptococcus, accompanying with decreased level of cytokines such as IFN-γ and IL-10, which was restored with varying degrees after standard treatment. This shift could become a predictive vaginal microbiota signature for C. trachomatis infection among tubal infertility females. Furthermore, we observed no significant differences in phylum, class and OUT levels between C. trachomatis-negative infertility women and healthy controls. This study provided the first data on the association of vaginal microbiota with C. trachomatis infection among tubal infertile women and highlighted unprecedented potential opportunities to predict C. trachomatis infection.